The Natural Product Andrographolide Ameliorates Calcific Aortic Valve Disease by Regulating the Proliferation of Valve Interstitial Cells via the MAPK-ERK Pathway - Huang, Yuming; Liu, Ming; Liu, Chungeng; Dong, Nianguo; Chen, Liang (Frontiers in Pharmacology, 2022)
Calcific aortic valve disease (CAVD) is an active pathobiological process at the cellular and molecular levels, which involves fibrosis and calcification of aortic valve leaflets causing hemodynamic changes in the heart and eventually contributing to heart failure. Cell proliferation changes during the process of CAVD at the initial stage are an important target for pharmaceutical intervention. The present study aimed to investigate whether andrographolide (AGP) could attenuate the cell proliferation of human valve interstitial cells to delay the process of CAVD. Cell proliferative factors were tested from healthy and CAVD aortic valve samples. Cell cycle, cell growth, and calcification of valve interstitial cells (VICs) were assessed using the flow cytometry, the CCK8 assay, the Edu staining, and Alizarin Red S staining respectively. The expression of the cell proliferative factors and osteogenic factors were quantified by qRT-PCR or immunofluorescent staining. Molecular docking was used to detect the interaction between AGP and ERK. High-fat feeding animal model to verify the effect of AGP on CAVD in vivo. We found Andrographolide ameliorates aortic valve incrassation by inhibiting cell proliferation via the MAPK-ERK signaling pathway. It is a potent drug that prevents the occurrence of heart valve calcification disease via regulating cell proliferation.